Fungal Skin Infections in Beach Volleyball Athletes in Greece - Niki Tertipi; Eleni Sfyri; Vasiliki Kefala; Efstathios Rallis (Hygiene)
Background/Objectives: Fungal infections, commonly referred to as mycoses, are widespread and affect various parts of the body. Common types of fungal skin infections include tinea pedis, tinea unguim, tinea cruris, tinea versicolor, and tinea manuum. Athletes, in particular, are at a higher risk of contracting these infections due to several factors inherent to their training and competitive environments. Methods: This research examined the incidence, anatomical distribution, and seasonal occurrence of fungal skin infections among beach volleyball athletes in Greece. The study cohort consisted of 785 participants, with an average age of 28.4 years. Variables recorded included gender, the seasonal periods during which athletes might be more prone to injuries, and the specific body areas affected by fungal infections. In addition, training-related data such as weekly training frequency, and daily training duration were collected. Results: Incidence rates correlated in relation to gender: male, tinea pedis (p < 0.000), tinea manuum (p < 0.010); number of weekly trainings: tinea pedis (p < 0.000), tinea unguium (p < 0.043), tinea cruris (p < 0.008), tinea versicolor (p < 0.038), tinea manuum (p < 0.043); average hours of daily training: tinea unguium (p < 0.039), tinea manuum (p < 0.039). Conclusions: Athletic activities often involve exposure to warm, moist conditions that promote fungal growth. Locker rooms, showers, and equipment can harbor fungi, spreading infections among athletes. Understanding these infections is essential for effective prevention and management, as they can impact performance and health if untreated. Proper hygiene, antifungal treatments, and public health measures are crucial to reducing the risk in athletic settings.